RETENÇÃO DE AMÔNIO EM RELAÇÃO À QUANTIDADE DE FOSFATO ADSORVIDO EM SOLOS LATOSSÓLICOS - Kinjo, Toshiaki; Silveira, Ronaldo Ivan; Kadekaru, Paulício K. (REVISTA DE AGRICULTURA, 2020)
RETENÇÃO DE AMÔNIO EM RELAÇÃO À QUANTIDADE DE FOSFATO ADSORVIDO EM SOLOS LATOSSÓLICOS